Film Coating of Small Molded Tablets for Pediatric Formulations with Rapid Disintegration and Bitterness-Masking Properties - Yuki Takahashi; Takayuki Furuishi; Etsuo Yonemochi (Molecules)
The bitter taste of drugs is an important impediment to medication adherence for pediatric patients. To develop a formulation that can be easily taken by pediatric patients, we prepared film-coated molded tablets to mask their bitterness and investigated their properties. We manufactured 5 and 3 mm film-coated tablets, which were easy for children to swallow. The tablets also exhibited rapid disintegration (≤30 s), making them suitable for tube administration. The formulation of the film-coating layer was experimentally optimized. Tablets (measuring 5 and 3 mm thick) containing the model drug dextromethorphan hydrobromide were film-coated by weight of the uncoated tablets (4% by weight). These tablets rapidly disintegrated and masked the bitterness for 10 s. An examination of the coated tablets revealed that the film covered the periphery, which may mask the bitterness. The findings demonstrate that coating small molded tablets with a film enables the manufacture of tablets that could be more tolerable for pediatric patients and suitable for tube administration.